Electrocatalysis of free chlorine on hydrogen oxidation - Kye Hak Ko; Kum Hyok Ri; Song Chol Jong; Wi Song Pak (Electrochemistry Communications)
A novel view of the electrocatalysis of free chlorine on hydrogen oxidation was proposed by cyclic voltammetry (CV) in seawater solutions. Since seawater has good pH buffering from its composition (bicarbonate, carbonate, borate, etc.), there is no need for the addition of any supporting electrolyte during voltammetric analysis. In CV experiment using a Pt disk electrode, the peak of hydrogen oxidation reaction (HOR) was formed at about −0.8 V during the reverse scan and its height has correlated with increasing contents of free chlorine present in seawater solution. All experimental results showed that free chlorine exhibited clear electrocatalysis on HOR. It gives the possibility of the determination of free chlorine using its electrocatalysis on HOR. Our attempt to quantify free chlorine by electrocatalysis of free chlorine on HOR is thus a new perspective compared to many studies that have been conducted on direct detection of free chlorine using its own electrochemical properties. In a new electroanalytical method of free chlorine using the Pt disk electrode, the corresponding calibration curve exhibited a linear response in the content range from 0.02 to 0.4 mg L−1 with a correlation coefficient of 0.998. The limit of detection (LOD) calculated from S/N = 3 was 0.012 mg L−1 and the relative standard deviation (RSD) obtained was 4.4 %.